2013
DOI: 10.2147/hiv.s43260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sociodemographic factors on cognitive function in school-aged HIV-infected Nigerian children

Abstract: BackgroundIn this study, we sought to evaluate the influence of sociodemographic factors, ie, age, sex, socioeconomic status, maternal education, and human immunodeficiency virus (HIV) status, on cognitive performance in school-aged HIV-infected Nigerian children.MethodsSixty-nine HIV-positive children aged 6–15 years were matched with 69 HIV-negative control children for age and sex. The children were subdivided for the purpose of analysis into two cognitive developmental stages using Piaget’s staging, ie, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…Two studies (Bisiacchi, Suppiej, & Laverda, 2000;Koekkoek et al, 2008) reported executive function deficits as the most sensitive cognitive measure in relation to HIV disease progression. A study by Koekkoek et al among 22 school-age children with HIV We identified a 16% prevalence of cognitive impairment in children with HIV infection, which is at variance with findings of 56% reported by Boyede in a study among Nigerian school-aged children (Boyede et al, 2013) and 71% reported by Puthanakit among Thai school-aged children (Puthanakit et al, 2013) with HIV infection (Puthanakit et al, 2013). In both studies the children were symptomatic of HIV infection and were on cART: 71% and 87% in Nigerian and Thai children, respectively.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Two studies (Bisiacchi, Suppiej, & Laverda, 2000;Koekkoek et al, 2008) reported executive function deficits as the most sensitive cognitive measure in relation to HIV disease progression. A study by Koekkoek et al among 22 school-age children with HIV We identified a 16% prevalence of cognitive impairment in children with HIV infection, which is at variance with findings of 56% reported by Boyede in a study among Nigerian school-aged children (Boyede et al, 2013) and 71% reported by Puthanakit among Thai school-aged children (Puthanakit et al, 2013) with HIV infection (Puthanakit et al, 2013). In both studies the children were symptomatic of HIV infection and were on cART: 71% and 87% in Nigerian and Thai children, respectively.…”
Section: Discussioncontrasting
confidence: 86%
“…A study by Coscia et al found that the quality of the home environment mediated the relationship between socioeconomic status and child cognitive function (Coscia et al, 2001), while a study conducted in Kenya among children under 3 years living in poverty reported anthropometric measures such as height and weight as mediators of the relationship between socioeconomic status and psychomotor development (Abubakar, 2008). We identified lower socioeconomic status as an independent risk factor for cognitive impairment in this study, a finding supported by previous research from resource-constrained settings (Bagenda et al, 2006;Boyede et al, 2013;Grantham-McGregor et al, 2007;Puthanakit et al, 2013). Poverty in the home has adverse effects on child development since it results in increased maternal stress or depression and inadequate child stimulation in the home (Grantham-McGregor et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Lowick et al () reported 90% of children between the ages of 5 and 6 years to be significantly delayed when tested with the Griffiths Scales of Mental Development (GSMD). In Nigeria, Boyede et al () found 56.5% of HIV‐infected school‐age children in their sample to perform below average on cognitive assessment. Children who have a diagnosis of HIV encephalopathy are more likely to present with cognitive impairment during childhood and adolescence (Smith et al ).…”
Section: Introductionmentioning
confidence: 99%